Changes in the Levels of Cytokines in Both Diabetic/Non-Diabetic Type I Children Living in a Moderate Altitude Area in Saudi Arabia - Allam, Gamal (Mary Ann Liebert, Inc., 2014)
Allam, Gamal, Adnan A. Alsulaimani, Hamed Alghamdi, Hameed Alswat, Burhan M. Edrees, Iftikhar Ahmad, and Amre Nasr. Changes in the levels of cytokines in both diabetic/non-diabetic type I children living in a moderate altitude area in Saudi Arabia. High Alt Med Biol 15:380–387, 2014.—The aim of the present study was to investigate the possible effects of living in moderate altitude area on pro/anti-inflammatory cytokines profile (IFN-γ, TNF-α, IL-6, IL-1β, IL-10, and IL-4) among type I diabetic (T1D) and non- T1D children compared with those living at sea level area. A prospective clinical study was carried out at pediatric outpatient endocrine clinics in Taif City, which is a moderate altitude area in Saudi Arabia, that stands about 1800–2000 meters above sea-level; and in Mecca City, which is a sea level area, that lies in the middle west of Saudi Arabia. Hemoglobin A1c (HbA1c) percentage was estimated and cytokine measurements were performed in sera by flow cytometry using Cytometric Bead Array (CBA) technology. In this study we included 600 children who were consecutively enrolled (sex and age were matched). The HbA1c was statistically significantly higher in children living in moderate altitude compared to those living at sea level (overall p<0.001). Furthermore, T1D patients had higher values of serum cytokine levels (IFN-γ, TNF-α, IL-6, IL-1β, IL-4, and IL-10) in comparison to non-T1D control group (overall p<0.001). In conclusion, the data of the present study clearly showed that in both T1D and non-T1D children, moderate altitude-natives expressed high HbA1c and both pro-and anti-inflammatory cytokines. Type I diabetic children living in moderate altitude or at sea level showed elevated levels of IFN-γ, TNF-α, IL-6, IL-1β, IL-4, and IL-10 than control subjects. Glycemic control in non-diabetic children was affected by living in moderate altitude, however, HbA1c significantly increased in diabetic children living in moderate altitude.